Mammal hibernation as a strategy for adaptation to unfavorable environmental conditions - A. K. Beibalaeva; Sh. I. Chalabov; N. K. Klichkhanov (Юг России: экология, развитие)
To analyse the literature data on the survival pathways of heterothermic endotherms in unfavorable environmental conditions, during periods of low availability of food resources.The article provides data on the differences between daily and seasonal heterothermy. The features of preparation for hibernation in facultative and obligate hibernators are highlighted. Hypotheses of the origin and evolution of heterothermy are considered. The most probable causes of periodic awakenings of animals from hibernation during the hibernation period are summarised. Considerable attention is paid to the restructuring of energy metabolism during hibernation – the transition from carbohydrate to lipid metabolism. Data have been analysed indicating the importance of fatty acids obtained from food during the active summer period, both for the synthesis of reserve fats and in the regulation of hibernation. Based on data on the accumulation of monoenoic fatty acids in tissues during hibernation, it has been suggested that they have an adaptive significance aimed at limiting oxidative stress and preserving vital cell functions.The data presented can be used both for conducting fundamental research on the adaptive mechanisms of interaction of an organism with its environment, and for solving practical problems, especially when choosing models of calorie restriction or intermittent fasting, as well as studying tissue tolerance to oxidative stress and resistance to the damaging effects of ischemia – reperfusion.